Communication as a Mobile Field: The Critical Dialogue and Exchange Between the Vatican Doctrine on Social Communication and Secular Communication Sciences - Arriola, Joyce (Archīum Ateneo, 2024)
The Decree on Social Communication called Inter Mirifica was one of the 16 documents that were produced by the Catholic Church at the Second Vatican Council (1962–1965). It guided the Church in engaging the modern world, particularly through the means of communication. This came at the height of the positivist inflection of communication studies, which began as an academic discipline when the first doctoral program was established in the United States in 1943. While the communication discipline grew steadily as a science, producing its own theories and adopting its specific research methodologies and protocols, it also developed along humanistic lines, largely through the efforts of the Media Studies scholars. While Inter Mirifica and other subsequent documents of the Church are anchored on a moral framework, secular communication studies remained positivist and value-neutral. This has created a tension but has somehow found a resolution within Media Studies, which flourished in the wake of the humanistic re-assertion of the claims of Classical Rhetoric and related theories. Enriched by cultural and political contexts that traverse continental and disciplinal divides, the critical dialogue and exchange between communication theology and secular communication studies have rendered both conceptually mobile and open to further reconfigurations.